Effects of mycorrhizal inoculation on growth of Acacia spp. planted on Beach Ridges Interspersed with Swales (BRIS) soils in Setiu, Terengganu, Malaysia - Mansor, Patahayah (2012)
Problematic soils such as Beach Ridges Interspersed Swales (BRIS) can be rehabilitated through planting of fast-growing and non site-demanding tree species. BRIS is an excessively drained soil, dominated by sand and has higher surface soil temperature, thus only selected species with the ability to tolerate harsh conditions can survive planting with minimal tending input on this site. Acacia species is one the best candidates for planting in such soil conditions and environments. It has the capability to fix the atmospheric nitrogen through root nodules and its roots can also form association with both ectomycorrhiza (ECM) and endomycorrhiza (AM). A 2.0-ha planting trial of Acacia spp. consisting of Acacia mangium, A.auriculiformis and the hybrid of both species, was established on Jambu series soil in Setiu, Terengganu, Malaysia. The aims of this trial were to determine the most suitable species of Acacia and the best mycorrhizal treatment for planting on BRIS soils. The trial consisted of four treatments i.e., T1-arbuscular mycorrhiza (AM inoculum application, T2-ectomycorrhizal inoculum (ECM) application, T3-AM + ECM application and T4-uninoculated control. All treatments were replicated four times. Survival rate and total height of the plants were monitored at three monthly intervals for the first year and at six-monthly interval thereafter up to 48 months. During the final measurement at 48 months, 48 plants, which represented 4 plants for each treatment, were destructively harvested for determination of biomass accumulation and nutrient uptake. Soil and root samples from each plot were also sampled for mycorrhizal assessment. At one year after planting, the relative growth rate of A. mangium was significantly (p<0.05) higher compared to the other two species. A. mangium showed best performance when arbuscular mycorrhiza was applied to, either in single or combination with ectomycorrhiza. However, growth of A. auriculiformis and Acacia hybrid were improved with the application of ectomycorrhiza. After 48 months outplanted, the Acacia hybrid showed the significantly (p<0.05) highest mean height followed by A. auriculiformis and A. mangium. The average mean height for the Acacia hybrid, A. auriculiformis and A. mangium were 711 cm, 453 cm and 390 cm respectively. Based on the chemical analysis of the foliage, the level of macronutrient concentrations were almost equal for all treatments except for N. Higher N concentration was observed in A. mangium of all treatments. This could be the influence from nitrogen fixing ability, which we expect to differ for each species. Root of inoculated AM showed the persistence of AM fungi in the plant roots and occurrence of AM fungal spores in the rhizosphere. The AM colonization found to be highest on A. mangium root and the spores were most abundance in the A.mangium rhizosphere, which ranged from 18 to 50 spores per 100g soil. However,no ECM presence was detected on roots of all treatments. The mean total biomass was highest in Acacia hybrid, but comparable for A.mangium and A. auriculiformis. Total biomass for Acacia hybrid, A. mangium and A.auriculiformis were ranged from 23.65 kg to 31.21 kg, 11.76 kg to 15.79 kg and 8.69 kg to 16.21 kg, respectively. The biomass distribution in the plant parts for all species found to concentrated most in the stem, followed by the root, branches and the least in the leaves. The stem biomasses of all species ranged from 38.3 to 49.6 %. Nutrient uptake was calculated based from the biomass accumulation. The nutrient uptake for all elements (N, P, K, Ca and Mg) was highest in Acacia hybrid and the dual mycorrhizal (ECM and AM) application found to significantly (p<0.05) enhanced the uptake of N, P and K in this species. In conclusion, based on the study, Acacia hybrid showed the best growth performance followed by A. mangium and A. auriculiformis when planted on BRIS soil. Different Acacia species however, showed different response towards different mycorrhizal inoculum. A. mangium performed best when applied with arbuscular mycorrhizal inoculum while application of ectomycorrhizal inoculum and combination of ectomycorrhiza and arbuscular mycorrhizas to A. auriculiformis and Acacia hybrid would improve their growth in BRIS soil. Therefore, the application mycorrhizas in plantation of forest tree species especially in the problematic and degraded soil are recommended. However, further study should be conducted to select the best mycorrhizal strain to be used and compatible with the tree host.